The Relationship between Age and Cerebral Atrophy on Head CT-Scan Examination at Haji Adam Malik General Hospital Medan - Imansyah, Ade Nur; Daulay, Elvita Rahmi; Surbakti, Khairul Putra (Journal of Society Medicine, 2024)
Introduction: Cerebral atrophy is a condition associated with brain volume reduction and is a common manifestation of aging. Age is an important factor in the incidence of cerebral atrophy. This research aims to know the relationship between age and the incidence of cerebral atrophy in patients at H. Adam Malik General Hospital Medan. Methods: This study is an observational analytic study with a cross-sectional design conducted at the Haji Adam Malik General Hospital Medan by collecting head CT scan data from the electronic medical records of 91 patients with the period January 1st 2021 to December 31st 2022. The research time will be carried out from October 2022 to December 2023. Results: Cerebral atrophy began to be found in the age group of 20-39 years, the largest gender was male (56%), the highest level of education in patients with cerebral atrophy was elementary school / equivalent (66.7%) and D1 to D3 (66.7%), and from the area of residence, patients who experienced cerebral atrophy mostly lived in urban areas (58.7%). The age of onset of cerebral atrophy was found to be 20 years old. The types of cerebral atrophy found in the study subjects were cortical atrophy as many as 49 people (53.8%) and global atrophy as many as 10 people (11%). There was no significant relationship between age and the incidence of cerebral atrophy in patients at H. Adam Malik General Hospital (p> 0.05), but there was a significant relationship between age group and the incidence of cerebral atrophy in patients at H. Adam Malik General Hospital (p < 0.05). Conclusion: There is no significant association between age and the incidence of cerebral atrophy in patients at Adam Malik General Hospital. Additional research is needed to gain a comprehensive understanding of cerebral atrophy and its relationship with other risk factors.